In Vitro Activities of Ceftobiprole, Dalbavancin, Tedizolid and Comparators against Clinical Isolates of Methicillin-Resistant Staphylococcus aureus Associated with Skin and Soft Tissue Infections - Sofia Maraki; Viktoria Eirini Mavromanolaki; Dimitra Stafylaki; Evangelia Iliaki-Giannakoudaki; George Hamilos (MDPI AG, 2023)
Skin and soft tissue infections (SSTIs) are associated with significant morbidity and healthcare costs, especially when caused by methicillin-resistant Staphylococcus aureus (MRSA). Vancomycin is a preferred antimicrobial therapy for the management of complicated SSTIs (cSSTIs) caused by MRSA, with linezolid and daptomycin regarded as alternative therapeutic options. Due to the increased rates of antimicrobial resistance in MRSA, several new antibiotics with activity against MRSA have been recently introduced in clinical practice, including ceftobiprole, dalbavancin, and tedizolid. We evaluated the in vitro activities of the aforementioned antibiotics against 124 clinical isolates of MRSA obtained from consecutive patients with SSTIs during the study period (2020-2022). Minimum inhibitory concentrations (MICs) for vancomycin, daptomycin, ceftobiprole, dalbavancin, linezolid and tedizolid were evaluated by the MIC Test Strip using Liofilchem strips. We found that when compared to the in vitro activity of vancomycin (MIC90 = 2 μg/mL), dalbavancin possessed the lowest MIC90 (MIC90 = 0.094 μg/mL), followed by tedizolid (MIC90 = 0.38 μg/mL), linezolid, ceftobiprole, and daptomycin (MIC90 = 1 μg/mL). Dalbavancin demonstrated significantly lower MIC50 and MIC90 values compared to vancomycin (0.064 vs. 1 and 0.094 vs. 2, respectively). Tedizolid exhibited an almost threefold greater level of in vitro activity than linezolid, and also had superior in vitro activity compared to ceftobiprole, daptomycin and vancomycin. Multidrug-resistant (MDR) phenotypes were detected among 71.8% of the isolates. In conclusion, ceftobiprole, dalbavancin and tedizolid exhibited potent activity against MRSA and are promising antimicrobials in the management of SSTIs caused by MRSA.